The ecology of an ecology project and some suggested adaptations for project survival - Peter Moodie (Southern African Journal of Environmental Education, 1987)
Mere dissemination of ecology teaching materials is likely to be ineffective in making the classroom teaching of ecology more meaningful. It may be necessary to take a more comprehensive view of the processes by which teachers change their practices. The article addresses both private sector and education department methods of innovation.